PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VII SMP MUHAMMADIYAH 1 PEKANBARU MELALUI PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH (PBM) - Arfah Unisa. S; Atma Murni; Zulkarnain Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of this research is the low of mathematical problem solving ability of first grade students in SMP Muhammadiyah 1 Pekanbaru. The purpose of this research are 1) to determine the significance of the improvement of mathematical problems solving ability of first grade students in SMP Muhammadiyah 1 Pekanbaru who were thought through problem based learning (PBL) model and saintific approach as usual learning; and 2) to determine the difference of the improvement mathematical problem solving ability of first grade students in SMP Muhammadiyah 1 Pekanbaru who were thought through PBL model and saintific approach as usual learning. This research used experiment and use design nonequivalent pretest-posttest control group design. Population in this research is all of the first grade students in SMP Muhammadiyah 1 Pekanbaru. Sample of this research consists of two classes, there are class VII6 as the class experiment and VII5 as the class control. The research instrument are the test of early mathematics ability obtained from the mean of daily test in odd semester and test of mathematical problem solving ability. The result of the early mathematics ability test is used to determination the class sample. Data were analyzed by normality test, homegenity of varians test, t-test, and Mann U Withney Test. The result showned that the improvement of mathematical problem solving ability of students who were thought through PBL model is higher than students who were thought through saintific approach as usual learning. The improvement of student’s mathematical problem solving ability through PBL model was categorized as medium while saintific approach was categorized as low.Key word: Problem Based Learning, Improvement of Mathematical Problem Solving Ability